The TRAIN Health Awareness Clinical Trial: Baseline Findings and Cardiovascular Risk Management in Aortic Dissection Patients - Bacour, Nora; Grewal, Simran; Tirpan, Aytug U.; Theijse, Rutger; Erp, Olivia Van; Klautz, Robert J.M.; Sakalihasan, Natzi; Hultgren, Rebecka; Grewal, Nimrat (AORTA, 2024)
Acute Type A aortic dissection (ATAAD) is a life-threatening condition requiring timely surgical intervention. Despite successful surgery, postoperative outcomes are frequently suboptimal due to the high frequency of cardiovascular risk factors. This study examines baseline cardiovascular risk factors in a population of ATAAD patients in the Netherlands. Additionally, this study outlines the protocol for a randomized controlled trial, designed to improve postoperative management.Baseline data were collected from patients with ATAAD. Data were gained through the Stichting Aorta Dissectie Nederland, a Dutch association for aortic dissection patients. The data included information on cardiovascular risk factors and health-related quality of life. A survey was further conducted, to gain more insights into the ATAAD postoperative care experiences of cardiac and vascular surgeons.Among the 50 ATAAD patients in our study, we found significant cardiovascular risk factors, including smoking (36.7%), obesity (34.2%), and hypertension (51.3%). In the surgeon survey (N = 48), 84% of respondents highlighted the significance of lifestyle changes for patients, underscoring the need for individualized risk management. These findings underscore the need for tailored postoperative management programs aimed at improving patient outcomes.The results of our study highlight that ATAAD patients require comprehensive postoperative care management strategies. The ultimate goal is to enhance long-term patient outcomes and improve health-related quality of life. To address this need, the TRAIN (Targeted caRdiovAscular rIsk reductioN) Health Awareness platform seeks to implement personalized eHealth-based lifestyle interventions.
Keywords: Type A aortic dissection; cardiovascular risk management; eHealth Interventions; lifestyle modifications; postoperative outcomes